Evaluation Of Early Versus Delayed Surgical Intervention Outcomes In Femoral Neck Fractures (The Review of Diabetic Studies, 2024)
This systematic review synthesizes available evidence on the impact of surgical timing in femoral neck fractures, particularly contrasting outcomes from early surgery, defined as intervention within 48 hours of injury, with delayed procedures beyond this threshold. The primary endpoints assessed were short- and long-term mortality rates, incidence of postoperative complications, and measures of functional recovery, all extracted in adherence to PRISMA-guided methodology. Data were drawn from multiple cohort studies and one large randomized trial encompassing a broad patient population across varying healthcare systems (Klestil et al., 2018; Warren et al., 2024). Across the included literature, early surgery appears to be associated with reduced long-term mortality in elderly patients, especially when performed within 48 hours of fracture occurrence. Studies with alternate cut-off thresholds such as 6, 12, or 36 hours failed to demonstrate differential survival outcomes, an observation that may reflect insufficient statistical power rather than genuine equivalence. No published study suggested a survival advantage with delayed surgery (Klestil et al., 2018). Results from the largest randomized controlled trial to date indicated comparable 90-day mortality rates between early and standard care groups when timing was guided by broader organizational criteria (Warren et al., 2024), illustrating the complexity in translating observational associations into uniform recommendations. Mortality patterns following hip fracture also intersect with specific patient factors such as preexisting comorbidities and physiological markers. Elevated perioperative C-reactive protein (CRP) levels have been linked in several reports to higher postoperative mortality (Chen et al., 2023), though disagreement persists due to inconsistent findings across studies. Anemia is another relevant factor; it tends to prolong recovery, worsen mobility outcomes, and heighten risk for fatal events after surgery (Clemmensen et al., 2021). These elements underline that surgical timing alone may not independently dictate prognosis but rather interacts with multiple patient-specific determinants. Postoperative complication profiles further inform the timing debate. Early mobilization after surgical repair correlates strongly with lower 30-day mortality and reduced complication rates. With more than 297,000 patients examined in aggregate analyses, these consistent benefits do not seem to extend substantially to length of hospital stay. Subgroup examination suggests that such advantages are only realized if true early ambulation is achieved rather than merely scheduled (Agarwal et al., 2024). This nuance emphasizes the importance of postoperative rehabilitation pacing alongside surgical scheduling. Functional recovery remains variably defined across observational datasets but consistently trends higher where surgery occurs before the two-day mark. This aligns with clinical guidance from bodies such as NICE advocating surgery on the day of or day after admission, a recommendation constructed on operational feasibility coupled with evidence synthesis indicating diminished adverse outcomes without identifying strict thresholds beyond which no benefit exists (Warren et al., 2024). The dataset underlying this analysis incorporates prospective cohort data lacking randomized control confirmation for many temporal thresholds (Klestil et al., 2018), signaling moderate to high risk-of-bias concerns in subsets of the literature. Despite PRISMA-compliant selection and dual independent review processes applied by included studies (Chen et al., 2023), heterogeneity remains considerable across some outcome measures. Aspects such as definitions for “early” versus “delayed” vary substantially among trials, impacting direct comparability. This review therefore presents a synthesis where timely (